Meninjau Ulang Motivasi Karyawan: dari Konsep Teoretis hingga Aplikasi Manajerial di Tempat Kerja Digital - Fatimah Rahman; Afrian Insan Kamil; Maliha Rizka Humaira; M Ramadhika Gautama Kartiwa; Sofa Parihah Nurasiah (Indo Publishing, 2026)
This study aims to revisit the concept of employee motivation, from classical motivational theories to their applications in the digital workplace. The study employed a qualitative literature review approach by systematically searching five academic databases, namely Scopus, Web of Science, ScienceDirect, Google Scholar, and Garuda. Articles were selected based on predefined inclusion and exclusion criteria, resulting in fifteen studies published between 2020 and 2026, complemented by several foundational theoretical works as the conceptual basis. The data were analyzed using a narrative synthesis approach involving theme identification, comparison of findings, and conceptual integration. The findings indicate that Self-Determination Theory remains the most relevant theoretical framework for explaining employee motivation in the digital era. Although digital transformation does not alter the fundamental psychological needs of autonomy, competence, and relatedness, it reshapes the mechanisms through which these needs are fulfilled through remote and hybrid work arrangements, algorithmic management, and gamification. The synthesis produced five conceptual propositions and an integrative framework explaining the relationships among digital workplace conditions, psychological need satisfaction, and motivational outcomes. This study contributes to the literature by integrating multiple dimensions of digital transformation into a unified conceptual framework grounded in Self-Determination Theory. It also offers practical implications for organizations in designing human resource policies and management practices that foster and sustain employees' intrinsic motivation in the digital workplace.